1969
DOI: 10.1111/j.1365-2494.1969.tb01071.x
|View full text |Cite
|
Sign up to set email alerts
|

The Carrying Capacity of Pastures

Abstract: The data from all published results of grazing trials in which three or more rates of stocking were compared for one or more years were examined. Where possible regression equations and correlation coefficients were calculated. In many cases, a significant negative correlation was found between stocking rate per acre and liveweight gain per animal per day. In no case was the relationship positive, and no point of discontinuity was found in the linear relationship. The slope of the line appeared to be related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 11 publications
3
23
1
1
Order By: Relevance
“…Over-grazing, as a concept -in terms of grassland management -indicates the grazing animal carrying capacity, the maximum number of tenable species/varieties per area unit, and the number of livestock kept for a period in order to produce needed product. An optimum stocking rate is the value, which regulate the number of grazing animals at the most economical rate (Cowlishaw, 1969). Over-grazing can be interpreted as an indicator of the actual number of livestock, but its time/interval defining dimension/role is more important (Pratt, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Over-grazing, as a concept -in terms of grassland management -indicates the grazing animal carrying capacity, the maximum number of tenable species/varieties per area unit, and the number of livestock kept for a period in order to produce needed product. An optimum stocking rate is the value, which regulate the number of grazing animals at the most economical rate (Cowlishaw, 1969). Over-grazing can be interpreted as an indicator of the actual number of livestock, but its time/interval defining dimension/role is more important (Pratt, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In 3 out of the 4 years the weight gain/animal was higher from treatment 0-6C than the expected straight line relationship between these two variables would have predicted (Riewe, 1961;Cowlishaw, 1969). 1970 gave an anomalous result for treatment 0-6C (see above).…”
Section: Resultsmentioning
confidence: 70%
“…Cowlishaw (1969) reviewed 22 trials, on a wide variety of pastures, and none revealed any discontinuities from a straight line relationship, except under very high grazing pressures, when the weight gain was sometimes lower than expected. In the current trial the highest stocking rate gave a higher gain than expected.…”
Section: Live-weight Gain and Stocking Ratementioning
confidence: 94%
“…We used the concept of carrying capacity (Cowlishaw, 1969) to characterize the sustainability of grazing. Carrying capacity, with respect to livestock grazing, refers to the number of grazing animals a landscape is able to support without depleting rangeland 102 vegetation or soil resources.…”
Section: Ecosystem Services Assessmentmentioning
confidence: 99%